Wandering Interns in Internship Sections - Mostafa Rad (Zanjan University of Medical Sciences and Health Services, 2018)
The main goal of nursing education is training nurses, who are able to care for clients in clinical settings. Clinical learning is an essential part of nursing education (1). The internship course of nursing students is training during work, where students learn through repetitive practice in clinical settings. This course is passing from being a student to being a nurse. In addition, the presence of interns somehow eliminates the need for workforce in clinical settings, despite the fact that this subject is not pointed out in the educational curriculum (2).